Giordano Bruno - szoboravatás
MTV Recording of the unveiling ceremony of Alexander Polzin’s statue at the CEU Residence and Conference Center in Budapest. The almost 7.5 m high bronze statue was commissioned in 2000 on the occasion of CEU founder George Soros’s 70th birthday and it commemorates the 400th anniversary of the death of Giordano Bruno. The ceremony opens with remarks by CEU Academic Pro-Rector Stefan Messmann. György Konrád, President of the Akademie der Künste in Berlin, then gives a brief address in honor of George Soros. In addition to CEU faculty, staff and students, a number of guests from outside the university were present. Among the guests were His Excellency Karl-Josef Rauber, the Apostolic Nuncio to Hungary, Minister Alexander von Rom representing the German Embassy, and Giorgio Pressburger, Director of the Italian Cultural Institute. President and Rector of CEU Yehuda Elkana was also present at the ceremony.